The performance of cattle stall-fed for beef in Malawi - Nkhonjera, L.P.; Agyemang, K.; Butterworth, M.H. (1987)
Presents and discusses a study on production and price on 2498 stallfed steers from the southern region and 2985 stallfed steers from the central region of Malawi which were on credit to smallholder farmers. Includes data on initial and final weight, total price and price/kg at beginning of feeding period & final grade; and dressing percentage and dressed weight price at end of feeding period and gross margin.